The Analysis on Students’ Difficulties in Doing Reading Comprehension Final Test - Ratih Laily Nurjanah (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2018)
Reading is one of skills considered important in language learning. But based on the condition in the classroom, reading skill is also influenced by some factors. This research is an attempt to find out the difficulties faced by students in doing reading comprehension to find the perfect technique or method to overcome the problem and answer the research questions (1) what difficulties are faced by students in doing reading comprehension test? (2) what are the causes of the difficulties? (3) what methods or learning activities are applicable in the classroom to overcome the difficulties?. The method of this study is explanatory multi-method strategy. The findings show that students face problem related to vocabulary knowledge or mastery. And they need more interactive learning activities. So here, the teachers should be more aware of problems faced by students and provide more interactive teaching techniques.